Entrepreneurial intent: A twelve-country evaluation of Ajzen's model of planned behavior - Engle, R.L.; Dimitriadi, N.; Gavidia, J.V.; Schlaegel, C.; Delanoe, S.; Alvarado, I.; He, X.; Buame, S.; Wolff, B. (Team Performance Management, 2010)
Purpose: The purpose of this paper is to test the ability of Ajzen's Theory of Planned Behavior to predict entrepreneurial intent in 12 countries representing all ten of the global regional clusters as identified in the GLOBE project. Design/methodology/approach: Ajzen's model was operationalized to address entrepreneurial intent and a questionnaire was developed consisting of previously used scales, as well as a new measure of entrepreneurial autonomy. A total of 1,748 usable questionnaires were collected from university business students in 12 countries. Findings: The results suggest that Ajzen's model of planned behavior, as operationalized in this study, does successfully predict entrepreneurial intent in each of the study countries, although as foreseen by Ajzen, the significant contributing model elements differ by country as does the percent of the variance explained by the model, although one model element, social norms, was a significant predictor of entrepreneurial intent in each country. Originality/value: This is the first paper to provide insight to the role of cognition in the entrepreneurial process by examining a model of planned behavior in countries representing all global regional culture clusters. The paper also provides guidance for future entrepreneurial research and individual development of entrepreneurs. © Emerald Group Publishing Limited.
Keywords: Behaviour; Cognition; Entrepreneurialism; Modelling; Social norms